A Research Based Of Supplementary Book in Tapak Tugurejo as Students’ Learning Resource on Mangrove Ecosystem Materials - Oktavia, Rizki; Iswari, Retno Sri; Alimah, Siti (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
This Research aims (1) to analyze the validity of supplementary book on research-based which is developed according to experts, media and user; (2) to analyze the effectiveness of supplementary book research-based to enhance the results of the study. This study used a modified Borg & Gall development model. The method used to analyze the validity of supplementary book, which is tested the components of feasibility and readability. The feasibility component test was given to materials experts, media experts and users, while the readability test was given to 27 students. The effectiveness of supplementary book is done in  SMA N 8 Semaang, using the Pre Experimental Design type One Group Pretest Posttest Design with a sample of 72 students. Validity and effectiveness test results were analyzed using quantitative descriptive method. Supplementary book effectively used in learning can be seen through KKM and N-Gain results. The results  shows that; (1) supplementary book on research based reach very valid criteria according to experts, media and user; (2) supplementary book on research based developed effective as  students learning outcomes proven by achieving 100% Minimum Criteria (KKM) and N-Gain in the medium criteria. This is also supported by affective aspects with excellent criteria and psychomotor aspects with highly skilled criteria. Supplementary book on research based on mangrove ecosystems are stated to be very valid and effective towards students? learning outcomes.